2012
DOI: 10.1371/journal.pntd.0001611
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Adaptive Immune Responses Are Associated with Latent Infections of Wuchereria bancrofti

Abstract: In order to guarantee the fulfillment of their complex lifecycle, adult filarial nematodes release millions of microfilariae (MF), which are taken up by mosquito vectors. The current strategy to eliminate lymphatic filariasis as a public health problem focuses upon interrupting this transmission through annual mass drug administration (MDA). It remains unclear however, how many rounds of MDA are required to achieve low enough levels of MF to cease transmission. Interestingly, with the development of further di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 66 publications
4
71
0
Order By: Relevance
“…Conversely, those cases succumbing to lymphatic pathology have deficient numbers of a key cell type, the regulatory T cell (Treg), while expressing stronger Th1 and Th17 effector components (14); the latter may be responsible for lymphatic inflammation against resident adult worms. Th17 cells are also more numerous in patients who have cleared bloodstream Mf (10), raising an interesting question of whether Mf directly downregulate Th17 responses and extend their survival by doing so.…”
Section: Immune Regulation and Spectrum Of Diseasementioning
confidence: 99%
“…Conversely, those cases succumbing to lymphatic pathology have deficient numbers of a key cell type, the regulatory T cell (Treg), while expressing stronger Th1 and Th17 effector components (14); the latter may be responsible for lymphatic inflammation against resident adult worms. Th17 cells are also more numerous in patients who have cleared bloodstream Mf (10), raising an interesting question of whether Mf directly downregulate Th17 responses and extend their survival by doing so.…”
Section: Immune Regulation and Spectrum Of Diseasementioning
confidence: 99%
“…Microfilaremia is higher in infected IL-4 KO, IL-5 KO, and IFNγ-KO mice, and intravenously inoculated microfilariae remain longer in the blood circulation before being cleared (Volkmann et al , 2001; Volkmann et al , 2003; Saeftel et al , 2003). In lymphatic filariasis infected individuals, TGF-βsingle nucleotide polymorphism has been associated with microfilaremic/amicrofilaremic status (Debrah et al , 2011) and latent infection of Wuchereria bancrofti has been shown to be associated with an elevated adaptive immune response (Arndts et al , 2012). This amicrofilaremic/microfilaremic profile is elegantly mirrored by mice models of filarial disease.…”
Section: Introductionmentioning
confidence: 99%
“…The release of Mf into the periphery signals the final stage of filarial nematode life cycles. Studies in individuals presenting asymptomatic W. bancrofti infections revealed that Mf + individuals had dampened immune responses following filarial‐specific activation when compared with Mf – cohorts . Infections in BALB/c mice with L. sigmodontis also results in Mf + and Mf – animals and this study shows that immune responses between these groups are different.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, only 50% of asymptomatic Wuchereria bancrofti ‐infected individuals become Mf + and as the Mf – group showed no overt signs of pathology this cohort remained largely undetected for many years. Although the reasons behind this phenomenon remain unclear the immunological profiles of these two cohorts are distinct . For example, when compared with Mf – individuals, peripheral blood mononuclear cells (PBMC) isolated from Mf + individuals displayed decreased tumour necrosis factor‐ α (TNF‐ α ), IL‐10 and IL‐5 upon filarial‐specific re‐stimulation .…”
Section: Introductionmentioning
confidence: 95%